If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
y+3 = (8/9)*(x-4) // - (8/9)*(x-4)
y-((8/9)*(x-4))+3 = 0
(-8/9)*(x-4)+y+3 = 0
y-8/9*(x-4)+3 = 0
y-8/9*(x-4)+3 = 0
y-8/9*x+3+32/9 = 0
y-8/9*x+59/9 = 0
y-8/9*x+59/9 = 0
y-8/9*x+59/9 = 0 // - y+59/9
-8/9*x = -(y+59/9) // : -8/9
x = (-(y+59/9))/(-8/9)
x = 9/8*(y+59/9)
x = 9/8*(y+59/9)
| 2(2-2x)= | | 3x+7=x-21 | | 3x+29-2x+4=-4x | | 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 | | 2(3x-4)=118 | | (4-1/2c)-1/3[3/4(1-2c)]1/12c | | 2x+5=-4x-6 | | (64m^1/2n÷m^-2n4/3)^1/2 | | 203/x=7 | | x/21=21 |